Emperors and Political Culture in Cassius Dio's Roman History - Davenport, Caillan (University of Cambridge ESOL Examinations, 2021)
A historical and historiographical study of the historian Cassius Dio and his account of political culture under the Roman Empire. Essential for students and scholars seeking to understand how Dio represented Roman emperors and their relationship with key groups such as courtiers, soldiers, and the people